ChemInform Abstract: Enantioselective Synthesis of α‐exo‐Methylene γ‐Butyrolactones via Chromium Catalysis. Issue 13 (March 2016) - Chen, Weiqiang; Yang, Qin; Zhou, Tian; Tian, Qingshan; Zhang, Guozhu
Abstract: Following a two‐step reaction sequence consisting of an asymmetric carbonyl 2‐(alkoxycarbonyl)allylation and lactonization, a variety of functionalized alkyl and aryl substituted products are prepared in high yields and with very high enantiomeric excesses.